Pengembangan Instrumen Tes Fisika untuk Mengukur Kemampuan Representasi Verbal Siswa SMA pada Materi Alat Optik - Pramudya Wahyu Pradana; Febriani Febriani; M. Ibnusaputra; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
In the context of Physics learning, verbal representation is very important to foster problem solving skills. However, the role of these representations has not been thoroughly measured and supported by good measurement instruments. In addition, the topic of optical instruments has concepts that can be expressed with verbal representations and is one of the important topics in physics. Therefore, in this study, an instrument was developed to measure students' verbal representation ability on optical instrument topic. The objectives of this research are to (1) determine the instrument's construction and (2) find out the feasibility of the instrument. The instrument was developed following the modified Wilson, Oriondo, and Antonio procedure through three stages: design, testing, and test preparation. The test was piloted on 88 randomly selected students who had studied optical instrument topic. The analysis carried out in this development includes content validity, item-model fit, reliability, and item difficulty level analysis. The development was successful in providing feasible test instrument items for evaluating students' verbal representation of optical instrument topic. This instrument is expected to be used to capture information about students' verbal representation ability, which will then be analyzed to produce more appropriate physics learning instructions.